Effect of salinity on growth, physiology, and production of groundcherry (Physalis angulata L.) - Diana N. Sholehah; Sucipto Hariyanto; Hery Purnobasuki (AIMS Agriculture and Food, 2022)
This study investigated the response of Physalis angulata L. to salt stress in terms of its growth, physiology, and production using a randomized block design with three replicates. For greenhouse cultivation, 21-day-old seedlings were cultivated in polybags containing Mediterranean soil and subjected to salinity treatments at concentrations set at 0, 20, 40, 60, 80,100,120,140,160, and 180 mM. Growth, physiology, and production parameters were measured 90 d after planting. Growth, stomatal density, yield, and fruit physical attributes were reduced at 80 mM and higher salinity. Salinity also increased the physiological responses and chemical features of the fruit. However, P. angulata grew faster and exhibited better yield and fruit quality at a salinity of 20 mM (2.25 dS m−1). Therefore, P. angulata can be cultivated in moderately saline soils, allowing for efficient land use.